A comparative study on the protective effects of ascorbic acid and tualang honey on the skin flap of reverse sural fasciocutaneous flap in a smoking rabbit model - Mohd Hussain, Mohd Shakir Bathusha (2015)
Lower limb traumas impose a great challenge for reconstructive surgeons. Complexity in the tissue constituent of lower limb and the concern regarding vascularity has been the barrier in the process of reconstruction. Introduction of pedicled fasciocutaneous flap based on reverse flow has provided an alternative to free flap reconstruction. Reverse sural fasciocutaneous flap is gaining popularity and widely being used in the reconstruction of distal third of lower limb due to its ease of elevation compared to free flap. Performing flap surgery in smokers has been proven to yield poor outcome. Components in cigarette smoke have an established negative impact on the vascular endothelium of blood vessels. Nicotine and carbon monoxide in cigarette smoke produce oxidative damage and release reactive oxygen species resulting in ischaemic injury. Ascorbic acid and “Tualang honey” are two agents which have been extensively studied for their anti oxidative and wound healing properties. Previous studies were aimed at studying the impact of cigarette smoke and ascorbic acid on the endothelium of large calibre vessel like carotid and aorta. The present study was undertaken to compare the anti oxidative properties of both these agents in improving the outcome in flap survival using a smoking rabbit model. This study is aimed at assessing the beneficial anti oxidative property to improve microvascular circulation in a reverse sural fasciocutaneous flap in a smoking rabbit model. All samples were exposed to cigarette smoke using a smoke chamber for a total of 5 weeks. Study sample was divided into three groups. Control group only received cigarette smoke while the other two groups each received ascorbic acid in the form of intramuscular injection and oral “Tualang honey” on top of exposure to cigarette smoke. Reverse sural fasciocutaneous flap was raised in all the rabbits at day 30 of exposure to cigarette smoke. Samples were evaluated on immediate post operative period, post operative day 1, 3 and 7. Parameters documented throughout the study were temperature, capillary refill time, colour of flap, presence hematoma or infection, and on post operative day 7 the flap survival was calculated. Intervention with smoking, ascorbic acid and “Tualang honey” were continued throughout the period of experiment. We found that, both group intervened with ascorbic acid and “Tualang honey” showed marked improvement in the flap survival. Statistically significant improvement were documented with regard to temperature, improvement in colour of flap and reduction in hematoma. Flap survival improved from 62% in the smoking arm to 88.9% and 81.0% in the ascorbic acid and “Tualang honey” arm. However oneway ANOVA test showed p value of 0.075 which was near to significant value. In conclusion both ascorbic acid and “Tualang honey” improved the survival of reverse sural fasciocutaneous flap in smoking rabbit model. However ascorbic acid is superior compared to “Tualang honey” in improving the oxidative damages produced by cigarette smoke and microvascular circulation of the reverse sural fasciocutaneous flap.